Antibody responses to an inactivated SARS-CoV-2 vaccine in individuals aged from 50 to 102 years - Zhu, Hong-Hong; Sun, Guo-Qing; Wu, Ji-Yu; Fan, Su-Qing; Zhu, Ying-Ying; Wang, Zhi-Cheng; Liao, Xiao-Fang (Frontiers in Immunology, 2023)
To assess antibody responses to SARS-CoV-2 vaccine in people aged 50 or older.We conducted a post-market cross-sectional seroepidemiology. We recruited 4,632 vaccinated people aged 50 or older, measured their serum SARS-CoV-2-specific total antibody (TA) and collected correlates. The primary outcome was the TA geometric mean titer (GMT) and the secondary outcome was the TA dwindling over age.Univariate, bivariate and multivariate analyses were used to examine the associations of the TA GMT with age and trend analyses were used to test their associations were significant.All participants had a detectable TA that was overall at a low level cross all age groups. The TA GMT (95% CI) in AU/mL was 3.05 (2.93, 3.18) (its corresponding arithmetic mean (95% CI) was 17.77 (16.13, 19.42)) in all participants and 4. 33 (3.88, 4.84), 3.86 (3.49, 4.28), 3.24 (2.92, 3.59), 2.77 (2.60, 2.96), and 2.65 (2.48, 2.83) in the age group of 50-54, 55-59, 60-64, 65-74, and 75 years or older, respectively. The TA GMT was decreasing over age with a P trend < 0.001. The TA GMT was significantly lower in those with hypertension, or diabetes compared to those with neither.Inactivated SARS-CoV-2 vaccine is effective to people aged 50 years or older. This is the first study that has found an inverse dose-response relationship between ages and 4 the low-level TAs. The old people, especially with chronic diseases, should get the SARS-CoV-2 vaccine and their vaccination frequency, dose, and method may need to be different from the young.